Representations of Banach algebras as algebras of completely bounded maps - Oikhberg, Timur (MATHEMATICA SCANDINAVICA, 2009)
We use the notion of $Π_2$-hyperreflexivity to construct, for a wide variety of Banach algebras $\mathcal A$, an operator space $X$ and a representation $π : {\mathcal A} → CB(X)$, such that $CB(X)$ consists of $2$-summing perturbations of $π({\mathcal A})$. This gives rise to some examples of operator spaces with interesting properties.